Comparing resident cataract surgery outcomes under novice versus experienced attending supervision - Puri S (Dove Medical Press, 2015)
Sidharth Puri,1 Amanda E Kiely,2 Jiangxia Wang,3 Alonzo S Woodfield,4 Saras Ramanathan,5 Shameema Sikder21Johns Hopkins School of Medicine, Baltimore, MD, 2Wilmer Eye Institute, Johns Hopkins University School of Medicine, Baltimore, MD, 3Bloomberg School of Public Health, Johns Hopkins University, Baltimore, MD, 4Kaiser Permanente South Sacramento Medical Center, Sacramento, 5San Francisco School of Medicine, University of California, San Francisco, CA, USAPurpose: To determine whether supervision by an attending new to surgical teaching or an experienced attending measurably influences intraoperative complications rates or outcomes in phacoemulsification performed by ophthalmology residents.Setting: Single tertiary hospital.Design: Retrospective cohort study. Methods: Resident-performed phacoemulsification cases supervised by one novice attending (N=189) and experienced attending (N=172) over 1 year were included. Data included: resident year, patient age, sex, preoperative risk factors (4+ dense/white/brunescent cataracts, Flomax, zonular dialysis, pseudoexfoliation, glaucoma risk, post-vitrectomy), intraoperative risk factors (Trypan blue, iris hooks), and intraoperative complications (capsule tears, vitreous loss, zonular dialysis, zonular dehiscence, burns, nuclear fragment loss, Descemet’s tear). Experienced attending data were compared against those of the novice attending.Results: Regarding preoperative risks, experienced attending cases more likely involved 4+ cataract (P=0.005), Flomax (P<0.001), or glaucoma risk (P=0.001). For intraoperative risks, novice attending cases more likely involved Trypan blue (P<0.001). Regarding complications, novice attending cases were associated with vitreous loss (P=0.002) and anterior capsule tears (P<0.001). When comparing total complications, the novice attending was more likely to have both increased number of cases with complications and total complications than the experienced attending. The novice attending’s overall complication rate trended downward (rate from 28% in first 25 cases to 6.67% in last 15).Conclusion: Early cases for the novice attending were accompanied by greater complications (vitreous loss and anterior capsule tear), likely due to a learning curve. Surgical judgment in the operating room likely develops with experience. Training programs may focus on these specific areas to aid new instructors. Keywords: cataract surgery, attending experience, complication rate